(3JMQjQ GdebGd aj ehGRfI GdCYeGd hMce ZjQ Gdecdajf aj GdYbHi hGdeBd aj GdQO Ydi GdMGaX GdMejOis - (3GdbVGYj , Ybjd Hf YWjI Hf LYaQ Hf eMeO Hf YWjI GdeQGcTj GdbVGYj, CHh GdeLO,J (B608 (3g` s ((3eMeO Hf YHO GdQMef Hf jMji s)
(3ChdgG (B:s
(3bGd GdbGVi CHh WGdH CeG HYO aEf CMO GdWdHI QYGge Gddg YQV Ydi cJGHkG UfYg CHh YHO Gddg eMeO Hf CHj fUQ GdMejQi s
(3BNQgG (B:s
(3hdcf GdMejQi RGO YdjgG HGdJJHY dgG hEVGaI eG TGcdgG MJi ESJMbgG Ydi Hf MRe s
(3GdfSNI HgG SJ hQbGJ ef UaMI (B13 _ 20 (3HNW fSN MOjKs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B290s
(3JHUQGJ GdCUd (B:s
(3bQFJ Ydi GdeDda SfI (B603 (3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK , CQVg , JQeje s
Keywords: (3GdJhMjO hGdedd hGdfMds